Evaluasi Penerapan Pengendalian Kualitas pada Proses Produksi UKM Sepatu Kulit di Kota Batam - Sumantika, Arsyad; Sirait, Ganda; Paskaria Lodya Tarigan , Elsya; Aji Prasetyo, Bahariandi (SURYA TEKNIKA, 2025)
This study evaluates quality control in leather shoe Small and Medium-sized Enterprises (SMEs) in Batam City using Failure Mode and Effects Analysis (FMEA) and Root Cause Analysis (RCA) methods. The background addresses product quality challenges affecting SME reputation and competitiveness. The research aims to identify potential failure modes, calculate Risk Priority Numbers (RPN), determine root causes, and formulate improvement recommendations. The methodology involves a hypothetical case study, applying FMEA to identify failure modes (Severity, Occurrence, Detection) and RCA (5 Whys, Fishbone Diagram) for root causes. FMEA results highlight "untidy/broken stitches" (RPN 360) and "cutting pattern errors" (RPN 336) as top priorities. RCA identified root causes such as insufficient operator training, suboptimal raw material procurement policies, inadequate machine maintenance, operator fatigue, and dull cutting tools. The study concludes by successfully identifying critical areas and root causes of quality issues. Recommendations include enhancing training, standardizing processes, preventive maintenance, and investing in precise equipment for SMEs.